2022
DOI: 10.7189/jogh.12.04066
|View full text |Cite
|
Sign up to set email alerts
|

How applicable is geospatial analysis in maternal and neonatal health in sub-Saharan Africa? A systematic review

Abstract: Background Sub-Saharan Africa (SSA) has the world's highest maternal and neonatal morbidity and mortality and has shown the slowest progress in reducing them. In addition, there is substantial inequality in terms of maternal and neonatal morbidity and mortality in the region. Geospatial studies can help prioritize scarce resources by pinpointing priority areas for implementation. This systematic review was conducted to explore the application of geospatial analysis to maternal and neonatal morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Additionally, it is assumed that emergency 4WD vehicles are present and immediately able to make emergency referrals. Whilst a common assumption, in reality, these vehicles are often unavailable in many parts of sub-Saharan Africa due to their upkeep and fuelling expenses, and they are often utilised in other tasks [ 19 , 133 ]. The model also assumes that all facilities have operational communications equipment with which to communicate referrals with [ 46 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is assumed that emergency 4WD vehicles are present and immediately able to make emergency referrals. Whilst a common assumption, in reality, these vehicles are often unavailable in many parts of sub-Saharan Africa due to their upkeep and fuelling expenses, and they are often utilised in other tasks [ 19 , 133 ]. The model also assumes that all facilities have operational communications equipment with which to communicate referrals with [ 46 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…These models can account for the impact of geographical barriers on health access when calculating population travel times and distances to health services. This approach is commonplace in maternal health research as geographic health access models are able to identify underserved populations, provide evidence to support interventions on improving accessibility, and identify the most influential geographical barriers to access [ 16 19 ]. For example, Ruktanonchai et al [ 1 ] used cost-distance analysis as part of their study investigating maternal healthcare utilisation, and found that increased geographical inaccessibility had the strongest association with reducing maternal care usage in five East African countries.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, for such modelling features to work, there is a need to ensure that the dashboard is interlinked with other databases [41]. A feature allowing modelling various provision scenarios such as HRH, cost of service provision, or service outcomes could extend the utility of the dashboard for service planning and allow it to be more informative for policymakers in their efforts to identify areas of inequalities in healthcare utilisation, achieve cost-efficiency in provision of maternal and newborn health services and reduce maternal and neonatal morbidity and mortality [42,43]. There are also other potential gains of a dashboard like this in SSA countries, including improving the routine health management information systems and enhancing accountability/ stewardship of health systems and policymakers toward the population, as was the case with the routine immunisation dashboard implemented in Nigeria [21].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the spatiotemporal characteristics of U5MR and the spatial spillover effect of health resources and services can comprehensively explain the long-term trend of health inequality in different countries in this region. It is of great significance to guide regional health planning and formulate regional health policies in West Africa, conducive to reducing child health inequality between and within countries ( 19 ). Hence, the present study aimed to describe the spatiotemporal characteristics of U5MR in 15 West African countries from 2010 to 2019 by combining the ecological design of geographic information systems and explore the spatial spillover effects of health resources and services on U5MR from the perspective of spatiotemporal correlation.…”
Section: Introductionmentioning
confidence: 99%